Study of injury and illness rates in multiday ultramarathon runners - Krabak, B. J.; Waite, B.; Schiff, M. A. (Medicine & Science in Sports & Exercise, 2011)
Purpose: This study aimed to describe injury and illness rates in runners competing in 7-d, 250-km off-road ultramarathon events.